Two arsenate resistance loci in the cellular slime mould Dictyostelium discoideum - Williams, K.L.
Fundamental to any genetic system is a series of markers from which a genetic map is constructed and which can be used to select regions of the genome. In simple eukaryotes auxotrophic mutations are often the markers of choice [1,2]. While a defined medium is established for some strains of Dictyostelium discoideum [3]and some auxotrophic mutations have been found [4], as yet none have been mapped. For technical reasons it is unlikely that auxotrophic mutations will be used extensively in D. discoideum genetics for some time. Instead three classes of selective mutations have been used: temperature-sensitivity mutations affecting growth [5,6], other sensitivity mutations [7,8]and resistance mutations [9-11]. In this report two arsenate resistance loci are established in D. discoideum. The arsenate resistance mutations alter the levels of sensitivity and resistance to several other compounds.